The Concept of Morality, Ihsan and Ta'dib in the Formation of Islamic Character and Malay Culture - Nafisah, Isri; Riadi, Haris; Suswanto; Khairina (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2025)
This study explores the fundamental concepts of morality (akhlaq), excellence (ihsan), and educational refinement (ta’dib) as integral elements in the development of Islamic character and their significant influence on the formation of Malay cultural identity. Employing a qualitative approach with descriptive and historical methods, data were collected through an extensive literature review related to Islamic concepts and Malay cultural traditions. The findings reveal that akhlaq, ihsan, and ta’dib play a vital role in shaping Islamic character within Malay society. Akhlaq serves as the foundation of religious and cultural education, fostering relationships between individuals, God, and others. Ihsanpromotes an awareness of God's presence in all actions, manifesting in social values such as mutual cooperation and respect. Ta’dib functions as an educational framework that instills profound moral and spiritual values, nurturing individuals of noble character. The application of these concepts strengthens Malay culture by aligning it with Islamic principles and preserving its noble values. In conclusion, reinforcing Islamic character through akhlaq, ihsan, and ta’dibis essential for sustaining and advancing Malay culture, ensuring that future generations remain grounded in Islamic values. Abstrak: Kajian ini membahas konsep dasar akhlak (moralitas), ihsan (kesempurnaan dalam beribadah dan berbuat baik), dan ta’dib (pendidikan adab) sebagai elemen penting dalam pembentukan karakter Islami serta pengaruhnya yang signifikan terhadap pembentukan budaya Melayu. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif dan historis, mengumpulkan data melalui studi pustaka yang berkaitan dengan konsep Islam dan budaya Melayu. Hasil penelitian menunjukkan bahwa Akhlak, Ihsan, dan Ta'dib memiliki peran penting dalam membentuk karakter Islami pada masyarakat Melayu. Akhlak menjadi dasar pendidikan agama dan budaya, menghubungkan individu dengan Tuhan dan sesama. Ihsan mengajarkan kesadaran akan kehadiran Tuhan dalam setiap tindakan, yang tercermin dalam nilai-nilai sosial seperti gotong royong dan saling menghormati. Ta'dib berfungsi sebagai pendekatan pendidikan yang menanamkan nilai moral dan spiritual tinggi, membentuk individu berakhlak mulia. Penerapan konsep-konsep ini memperkuat budaya Melayu yang berbasis pada ajaran Islam, menjaga nilai-nilai luhur dalam masyarakat. penguatan karakter Islami melalui Akhlak, Ihsan, dan Ta'dib sangat penting dalam mempertahankan dan mengembangkan budaya Melayu, memastikan generasi mendatang tetap berpegang pada prinsip-prinsip Islam.